Nestor Maksimovich Maksimovich-Ambodik - S. R. Magomedova; A. E. Alkhimova; A. V. Vorobev (Акушерство, гинекология и репродукция, 2024)
Here, we describe the historical aspects of Nestor Maksimovich Maksimovich-Ambodik life and scientific work, as well as describe his contribution to the formation and development of obstetrics and gynecology in the Russian Empire.